2018
DOI: 10.1177/0361684318792853
|View full text |Cite
|
Sign up to set email alerts
|

Eating Attitudes of Women Living With a Vision Impairment

Abstract: Internalization of cultural standards of attractiveness and subscription to gender-based discourses are significant predictors of disordered eating attitudes in fully sighted women. Yet, whether these variables predict the disordered eating attitudes of women who are legally blind is underexplored. In the current study, we examined how internalization of White European cultural standards of attractiveness and subscription to gender-based discourses (body surveillance and self-silencing) and body shame predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…In addition, they reported enhanced perceived pressure to conform to these ideals, as well as stronger internalization, which was unobserved in blind individuals. Late-blind women showed comparable levels of internalization of general and athletic body ideals typically conveyed through the media, suggesting that previous visual experience is sufficient to prime metric body representations (Longo & Haggard, 2012) that may serve at a level of social comparison (Longo & Haggard, 2012; Nava et al, 2021; Page & Papps, 2018). It further highlights the idea that females living with vision impairment are as predisposed to internalizing unhealthy ideals as sighted females.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, they reported enhanced perceived pressure to conform to these ideals, as well as stronger internalization, which was unobserved in blind individuals. Late-blind women showed comparable levels of internalization of general and athletic body ideals typically conveyed through the media, suggesting that previous visual experience is sufficient to prime metric body representations (Longo & Haggard, 2012) that may serve at a level of social comparison (Longo & Haggard, 2012; Nava et al, 2021; Page & Papps, 2018). It further highlights the idea that females living with vision impairment are as predisposed to internalizing unhealthy ideals as sighted females.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research showed that congenitally blind women, who are unable to access visual images of body ideals, have higher body satisfaction than sighted women, implying that limited exposure to visual media may offer some protection from developing concerns around body image (Ashikali & Dittmar, 2012;Baker et al, 1998;Gebauer et al, 2019). Other findings suggest that women with congenital and adventitious blindness may be as prone to internalizing messages on sociocultural idealizations as sighted women (Page & Papps, 2018;Simeunovic Ostojic & Hansen, 2013), confirming that the negative effect of social comparison does not require visual input (Gaudio et al, 2014;Touyz et al, 1988) and may be enhanced through other psychosocial factors (Simeunovic Ostojic & Hansen, 2013). Hence, the notion that restricted access to visual beauty idealizations results in decreased internalization of unhealthy messages and consequently higher body satisfaction is undoubtedly in question.…”
mentioning
confidence: 99%